1993
DOI: 10.21273/hortsci.28.8.774
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Affects Cowpea and Okra Seed Emergence and -Growth at Low Temperatures

Abstract: The effect of moisture content on the emergence and development of `Pinkeye Purple Hull' and MN 13 cowpea [Vigna unguiculata (L.) Walp.] and `Clemson Spineless' okra [Abelmoschus esculentus (L.) Moench] seeds was investigated in a 3-year field study. Moisture content, ranging from 8% to 52%, was obtained by combining seeds, vermiculite, and varying volumes of water in sealed polyethylene packets and incubating them at 22C for 3 days. High moisture p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Having diverse potential applications, SMP not only increases the germination performance of seeds, but also provide a delivery system for selective fungicides and bio-control organisms to control various soil-borne pathogens (Harman and Taylor, 1988). Moreover, for improving seed emergence SMP could be used as a pre-sowing seed treatment when sown in cold soils especially for the plants sensitive to cool temperature (Marsh, 1993). Priming could allow greater membrane integrity in the embryo as a result of which the developing seedlings reduce ion leakage through the membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Having diverse potential applications, SMP not only increases the germination performance of seeds, but also provide a delivery system for selective fungicides and bio-control organisms to control various soil-borne pathogens (Harman and Taylor, 1988). Moreover, for improving seed emergence SMP could be used as a pre-sowing seed treatment when sown in cold soils especially for the plants sensitive to cool temperature (Marsh, 1993). Priming could allow greater membrane integrity in the embryo as a result of which the developing seedlings reduce ion leakage through the membranes.…”
Section: Discussionmentioning
confidence: 99%
“…High moisture content usually leads to seed dormancy. Marsh (1993) The virus produces typical vein yellowing and thickening of leaves forming a network of veins and veinlets in the infected leaves. In the beginning, the leaves exhibit only yellow colored veins but under severe infection, the leaves become completely chlorotic and turn yellow.…”
Section: VImentioning
confidence: 99%
“…Sionit et al, (1981) reported seed germination for okra (Clemson spineless) at 16/11, 20/14 and 23/17 °C day/night temperature, with the lowest temperature delayed the emergence. Lurline Marsh (1993) studied the effect of moisture content on the emergence and development of okra seeds and found that high moisture decreased the emergence of okra seeds. Anderson (2012) found that selection of a hybrid that germinates early under favorable temperature and then weeds would not offer competition, is the most efficient method for achieving good establishment.…”
Section: Germination and Emergencementioning
confidence: 99%